2017
DOI: 10.1086/690908
|View full text |Cite
|
Sign up to set email alerts
|

Determining Selection across Heterogeneous Landscapes: A Perturbation-Based Method and Its Application to Modeling Evolution in Space

Abstract: Online enhancements: appendixes.abstract: Spatial structure can decisively influence the way evolutionary processes unfold. To date, several methods have been used to study evolution in spatial systems, including population genetics, quantitative genetics, moment-closure approximations, and individualbased models. Here we extend the study of spatial evolutionary dynamics to eco-evolutionary models based on reaction-diffusion equations and adaptive dynamics. Specifically, we derive expressions for the strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 75 publications
1
31
0
Order By: Relevance
“…For substitutable resources (trueκ^normalZ<1), diversity declines abruptly at the diagonal trueκ^normalZ=trueκ^normalT, where the system undergoes a shift in selection regime. To understand this regime shift, we use ideas from Wickman et al (), who showed that selection in spatially heterogeneous systems described by reaction‐diffusion equations can be divided into sympatric and parapatric selection terms. Sympatric selection is a spatially weighted average of local disrupting or stabilising selection, and parapatric selection is, roughly speaking, a measure of the variance in local directional selection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For substitutable resources (trueκ^normalZ<1), diversity declines abruptly at the diagonal trueκ^normalZ=trueκ^normalT, where the system undergoes a shift in selection regime. To understand this regime shift, we use ideas from Wickman et al (), who showed that selection in spatially heterogeneous systems described by reaction‐diffusion equations can be divided into sympatric and parapatric selection terms. Sympatric selection is a spatially weighted average of local disrupting or stabilising selection, and parapatric selection is, roughly speaking, a measure of the variance in local directional selection.…”
Section: Resultsmentioning
confidence: 99%
“…Ecologically, low or no movement corresponds to the species sorting scenario of metacommunity theory (Leibold et al ), for which regional coexistence of many resource competitors is possible if the landscape contains a broad range of local resource supply ratios (Tilman ). Wickman et al () showed that this also holds evolutionarily for perfectly substitutable resources and generalist‐favouring trade‐offs. The number of evolutionarily coexisting consumers increases as diffusion rates decrease, and as diffusion rates approach zero, an infinite number of consumers can coexist, which adapt locally to a continuum of spatially varying supply ratios (Wickman et al ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, they may be derived from density-and frequency-dependent interactions among phenotypes, in which case the relative advantage of a trait x against a different trait y depends on the context of their interaction. For instance, in [9,13,17,29] the invasion fitness between phenotypes with different dispersal strategies is obtained in the context of reaction-diffusion equations modeling the two competiting species in a bounded spatial domain. Those results concerning pairwise interactions has implications in the mutation-selection framework [12,11,18,19,24], which concerns populations structured by space and trait.…”
mentioning
confidence: 99%